The influence of technology on entrepreneurial self-efficacy development for online business start-up in developing nations. (August 2020) - van der Westhuizen, Thea; Goyayi, Marialauda Joel
Business start-ups are usually volatile and risky. They require rapid response and adaptability, calling for entrepreneurial self-confidence among young entrepreneurs. As there is a presumption that technology can alleviate these challenges, this study assessed transformation in entrepreneurial self-efficacy (ESE) among young South Africans in relation to an online business start-up. The article's contribution centres on the advancement of knowledge on youth entrepreneurship development by understanding/exploring the impact of technology in boosting entrepreneurial confidence and thus stimulating entrepreneurial activities. Using an action learning approach, a business tech start-up process was simulated with a group of 109 randomly recruited participants. Their ESE moving through the start-up cycle was captured and analysed. Likert-scale data were collected on their perceptions before and after the simulation in relation to tolerance self-efficacy, relationship self-efficacy, managerial self-efficacy and opportunity identification self-efficacy. Findings showed significant change in ESE for business start-up after exposure to the potentials and opportunities of technology-related businesses. Participants showed increased confidence and enthusiasm on prospects of success in establishing tech businesses. Effect on the development of ESE was also more pronounced in male participants than female participants.